Computer Network Security Based on IP Identification and Improved Ant Colony Algorithm - Chunfeng, Jiang (2023 4th International Conference on Smart Electronics and Communication (ICOSEC), 2023)
Network security analysis is the first step in network security management. In order to adapt to the increasing size of the network and the increasingly complex network environment, a lot of work has to be done in the generation of attack graphs. Based on this, the paper proposes the computer network security model based on IP identification and improved ant colony algorithm. The proposed algorithm has the 2 major steps: 1. IP Identification Algorithm. The network tomography-based identification method and the IP network router identification method are combined to form the network tomography-based IP network router is proposed to make the accurate recognition of IP 2. Improved Ant Colony Algorithm for Computer Network Security Modelling. We consider optimizing the heuristic function, for the feature attribute data points that can be added to the current rule for improving the algorithm and model performance. In the experiment section, the comparison tests regarding the Average Detection Rate and Average Error Rate are conducted to show the robustness of the proposed model.